2013
DOI: 10.5709/ce.1897-9254.127
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Apply Multidimensional Graphical Methods in The Teaching and Learning of Economics?

Abstract: This article explores the effectiveness of applying a new multidimensional graphical method to the teaching and learning of economics. In essence, the paper extends the significance of multi-dimensional graphs to study any economic phenomenon from a multidimensional perspective. The paper proposes the introduction of a new set of multidimensional coordinate spaces that should clearly and logically propose the effective visualization of complex and dynamic economic phenomena into the same graphical space and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This presumes that graphs facilitate learning about pricing by illustrating and simplifying complex processes and relations (Wheat, 2007b). However, research has identified challenges posed to students by this practice and has questioned whether students' learning is helped or hindered by the use of graphs (see, for instance, Cohn et al, 2001Cohn et al, , 2004Colander, 1991;Davies, 2012;Davies & Mangan, 2013;Estrada, 2013;Kourilsky & Wittrock, 1987;Reingewertz, 2013;Strober & Cook, 1992;Zetland et al, 2010). A critical problem with supply/demand graphs is that they portray dynamic relationships in terms of "comparative statics".…”
Section: Earlier Research: Learning About Price Through Visual Represmentioning
confidence: 99%
“…This presumes that graphs facilitate learning about pricing by illustrating and simplifying complex processes and relations (Wheat, 2007b). However, research has identified challenges posed to students by this practice and has questioned whether students' learning is helped or hindered by the use of graphs (see, for instance, Cohn et al, 2001Cohn et al, , 2004Colander, 1991;Davies, 2012;Davies & Mangan, 2013;Estrada, 2013;Kourilsky & Wittrock, 1987;Reingewertz, 2013;Strober & Cook, 1992;Zetland et al, 2010). A critical problem with supply/demand graphs is that they portray dynamic relationships in terms of "comparative statics".…”
Section: Earlier Research: Learning About Price Through Visual Represmentioning
confidence: 99%
“…In fact, the application of the Omnia Mobilis assumption (Ruiz Estrada, 2011) is the basic condition to generate the real time effect of the NP-Function. Hence, the final national output "Y * " always remains dynamic with multi-dimensional behavior according to the economic modeling in real time in its multi-dimensional space (Ruiz Estrada, 2013). Finally, the analysis of the result of the NP-Function depends on the position of the surface, which can help to determine the situation of any economy.…”
Section: The National Production Function (Np-function)mentioning
confidence: 99%